Exploring subjective happiness, life satisfaction, and sustainable luxury consumption in China and Japan amidst the COVID-19 pandemic - Kyung Tae Lee; Hiroyasu Furukawa (Administrative Sciences, 2023)
The COVID-19 pandemic has significantly impacted societies worldwide, leading to challenges in ensuring well-being and sustainability. In this context, it is essential to better understand consumer consciousness of pro-environmental products from the perspective of well-being. Therefore, our cross-national investigation aimed to explore the relationship between subjective well-being (SWB) and sustainable luxury consumption during the pandemic. We analyzed data from 800 respondents in China and Japan during the pandemic. Our findings, obtained through partial least squares structural equation modeling, reveal novel insights. First, SWB positively influences pro-environmental behavioral intentions, even in luxury fashion consumption. This highlights the potential for individuals to make sustainable choices, while indulging in luxury products. Additionally, we observed variations in the impact of subjective happiness and life satisfaction on luxury consumption between China and Japan. Specifically, the influence of subjective happiness was more pronounced in China than in Japan, indicating cultural distinctions in the relationship between well-being and luxury consumption. Moreover, our study identifies consumer novelty seeking as a mediator linking SWB to sustainable luxury consumption. This discovery provides a further understanding of the relationships explored in our study. These findings deepen our understanding of the interplay between well-being and sustainable luxury consumption, thereby informing strategies to promote pro-environmental behaviors in the luxury fashion sector.
Keywords: 350; consumer novelty seeking; COVID-19; life satisfaction; purchase intention of sustainable luxuries; subjective happiness; subjective well-being